2022
DOI: 10.1097/qai.0000000000003012
|View full text |Cite
|
Sign up to set email alerts
|

HIV Pre-exposure Prophylaxis Uptake and Continuation Among Key Populations in Cameroon: Lessons Learned From the CHAMP Program

Abstract: Introduction: Pre-exposure prophylaxis (PrEP) is proven to be a highly effective HIV prevention method for key populations. However, its scale-up in resource-limited settings remains suboptimal. This paper seeks to describe PrEP initiation and continuation among key populations in Cameroon.Methodology: From June 2019 through October 2020, we collected routine program data on PrEP uptake and continuation among female sex workers (FSWs) and men who have sex with men (MSM) in the Continuum of prevention, care and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…For each determinant, we adapted the shortest available scale with the goal of including a diverse and informative set of variables at the expense of losing some precision which might also explain, in part, the relatively low percentage of variance explained for intention to use PrEP. Finally, intention to use PrEP does not always correlate with PrEP initiation and adherence (i.e., the so-called "intention-behavior gap"); meaning that determinants identified in our study might differ from the ones associated with effective PrEP usage (Ndenkeh et al 2022;Witte et al 2022;;Sheeran and Webb 2016).…”
Section: Limitationsmentioning
confidence: 61%
See 2 more Smart Citations
“…For each determinant, we adapted the shortest available scale with the goal of including a diverse and informative set of variables at the expense of losing some precision which might also explain, in part, the relatively low percentage of variance explained for intention to use PrEP. Finally, intention to use PrEP does not always correlate with PrEP initiation and adherence (i.e., the so-called "intention-behavior gap"); meaning that determinants identified in our study might differ from the ones associated with effective PrEP usage (Ndenkeh et al 2022;Witte et al 2022;;Sheeran and Webb 2016).…”
Section: Limitationsmentioning
confidence: 61%
“…It is known that FSWs in Spain do suffer from stigma that can impact their access to PrEP services (AsociaciĂłn Pro Derechos Humanos de AndalucĂ­a n.d.) with more than half of the study participants not reporting their occupation to health care providers when it would be appropriate to do so. Some additional things to consider in future studies are the impact of side-effects (not significant in the analysis, but found to be a primary reason to decline initiation or continuation of oral PrEP among FSWs in previous studies) (Amogne et al 2022;Ndenkeh et al 2022;Reza-Paul et al 2020;Sarr et al 2020), and the need for integration of family planning services within PrEP programs given the low pre-existing use of contraceptive methods other than condoms in the study cohort.…”
Section: Intention To Use Prep and Prep Delivery Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional strategies for prevention are needed to achieve progress in addressing the HIV epidemic among MSM in Cameroon. PrEP coverage in Cameroon is currently low, since programs only began to be implemented in 2019 alongside the inclusion of PrEP in the national strategic plan for HIV[ 26 ]. Given the high risk of HIV among MSM, PrEP represents an additional intervention to be included among a suite of biological, behavioural, and structural interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Scale up of PrEP initiated in early 2021 in six cities with high concentrated key populations including Bafoussam, NgaoundĂ©rĂ©, Kribi, Bertoua, Bamenda and Buea. Although PrEP has not yet been widely available in Cameroon, the new national HIV strategic plan has included PrEP as an intervention for HIV prevention for MSM and female sex workers [ 26 ]. Therefore, modeling the potential impact of PrEP on HIV prevalence in the two largest cities in Cameroon can help inform the level of implementation needed to achieve prevention outcomes.…”
Section: Introductionmentioning
confidence: 99%